Nutritional composition and sensory evaluation of tempeh from different combinations of beans - Z.J, Tan; M.F, Abu Bakar; S.Y, Lim; H, Sutimin (2024)
Tempeh is recognised as an excellent source of plant protein and a promising meat substitute in the diet. Recently, the development of tempeh by blending different legumes has gained more attention, but references are limited. This study aimed to develop tempeh combinations of soybean with chickpeas and red kidney beans. The physical characteristics of the tempeh samples were recorded, and their nutritional compositions were determined in accordance with the standard AOAC methods. A sensory evaluation was also conducted by using the hedonic 9-scale test to study the overall acceptance of the tempeh. Our results indicated that the soybean and chickpea tempeh combination contained 31.08±0.41% protein, 9.88±1.42% fat, 16.57±1.90% carbohydrates, 13.49±0.03% crude fibre, 4.40±0.02% dietary fibre, 39.91±0.23% moisture, and 2.57±0.21% ash content per 100 g. Meanwhile, the soybean and red kidney bean tempeh combination had 30.39±0.12% protein, 9.43±1.02% fat, 13.31±0.78% carbohydrates, 11.88±0.03% crude fibre, 2.50±0.02% dietary fibre, 44.17±0.03% moisture, and 2.70±0.26% ash content per 100 g. Both mixed bean tempeh samples demonstrated high nutritional value. However, the sensory evaluation showed that the soybean and red kidney bean tempeh combination was preferred by most panellists due to its appearance, texture, taste, and aroma, with the highest overall acceptance score (7.54±0.85). In conclusion, our study highlights the potential of blending soybean with chickpeas and red kidney beans to develop tempeh with a high nutritional value. These findings could have significant implications for developing plant-based meat substitutes with desirable nutritional and sensory properties.